Fairy tail. 28 - Mashima, Hiro, 1977- (Kodansha Comics, 2013)
"Erza is up against Azuma, a dark wizard who uses trees as conduits to draw upon the magic of the earth itself. He uses this mysterious power to fell the great tree at the heart of Sirius Island, depriving all the Fairy Tail wizards of their magic! Can a nearly powerless Erza hope to stand against him? And where has Zeref the Black Wizard gone?" -- from publisher's web site.